Mechanical Properties of Lightweight EPS Self-compacting Concrete Reinforced with Steel Fibers (Journal of Engineering, 2024)
This study aims to evaluate experimentally the mechanical characteristics of Self-Compacting Concrete (SCC) comprising expanded polystyrene beads (EPS) to produce flowable lightweight concrete reinforced with steel fibers. In this paper, the effect of steel fibers and EPS content on the fresh and hardened mechanical properties of SCC specimens, using two percentages for Polystyrene aggregate replacement (25% and 50%) and three values for volume fraction of steel fiber content (0%, 0.75%, and 1.5%), were examined. Fresh mixture properties were determined using slump flow, L-box, and V-funnel tests. Mechanical properties for hardened samples were obtained using standard specimens for compressive strength, density, split, and flexural strength. The study showed that EPS content has no adverse effect on the rheological features of the SCC. However, workability falls below specification limits when adding steel fibers to SCC. Results revealed that using 25% of EPS content resulted in lightweight structural concrete, while lightweight moderate-strength concrete was produced using 50% of EPS content. Furthermore, the study has shown that the split and flexural tensile strength were reduced substantially by 53% and 60% due to EPS addition. However, adding steel fibers remarkably improved the indirect tensile strength and Modulus of rupture by 46% and 80%, respectively. The mode of failure of the concrete specimens containing EPS beads and steel fibers did not show brittle failure behavior generally encountered in normal-weight concrete, indicating a more ductile behavior.